Предмет:
МатематикаАвтор:
аноним1) Домножим исходное равенство на:
2 * (x/2 + π/4) = 2 * (π/2 + π * n).
Раскрыв скобки, получим:
x + π/2 = π + 2πn.
Перенесем π/2 в правую часть:
x = π - π/2 + 2πn = π/2 + 2πn.
2) Домножим на 2/5:
x - 2π/20 = 2 * π * n /5;
x - π/10 = 2 * π * n /5;
x = π/10 + 2 * π * n /5.
Автор:
seth57Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть